2014
DOI: 10.1097/mpa.0b013e3182a63b9d
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Fucoidan, a P- and L-Selectin Inhibitor, in Murine Acute Pancreatitis

Abstract: Fucoidan reduced the severity of acute pancreatitis in mice by decreasing neutrophil infiltration and systemic inflammation, suggesting that modulation of selectins may constitute a promising therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…The levels of cytokines and MPO were significantly reduced showing its pharmacological effect. The intervention attenuated histological pattern in both the models thus supporting the biochemical results (Carvalho et al , ). Hence, inhibition of P‐selectins may prove to be a novel approach to combat the inflammation associated with AP.…”
Section: Herbal Remedies Used For Treating Pancreatitissupporting
confidence: 84%
“…The levels of cytokines and MPO were significantly reduced showing its pharmacological effect. The intervention attenuated histological pattern in both the models thus supporting the biochemical results (Carvalho et al , ). Hence, inhibition of P‐selectins may prove to be a novel approach to combat the inflammation associated with AP.…”
Section: Herbal Remedies Used For Treating Pancreatitissupporting
confidence: 84%
“…Not only did the oral formulations alleviate the macroscopic pathologies such as body weight and stool consistency, they also significantly reduced the underlying intestinal inflammation. Although previous reports have demonstrated anti-inflammatory activities of fucoidan and fucoidan-containing extracts in different experimental models in vitro and in vivo [18, 22, 3136], this is the first report to demonstrate that dietary fucoidan extracts from Fucus vesiculosus are highly effective in ameliorating experimental colitis through a consistent downregulation of a significant number of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 72%
“…However, we demonstrated that only fucoidans derived from U. pinnatifida and M. pyrifera could inhibit neutrophil apoptosis at low concentration. The most plausible hypothesis to explain the specific inhibitory effect of fucoidans on neutrophil apoptosis could be their ability to react with L- and P-selectins on neutrophils [ 19 ]. It is well-established that L-selectin is efficiently shed from the surface of neutrophils and down-regulation of L-selectin is induced during programmed neutrophil apoptosis [ 20 ].…”
Section: Resultsmentioning
confidence: 99%